Validity and reliability of capillary vs. Venous blood for the assessment of haemoglobin mass and intravascular volumes - Royal, Joshua T.; Fisher, Jason T.; Mlinar, Tinkara; Mekjavic, Igor B.; McDonnell, Adam C. (Frontiers in Physiology, 2022)
Objectives Haemoglobin mass (Hbmass) assessment with the carbon monoxide rebreathing method is a more accurate estimate than other measures of oxygen-carrying capacity. Blood may be collected by several means and differences in the measured variables may exist as a result. The present study assessed the validity and reliability of calculated Hbmass and intravascular volumes obtained from capillary blood (CAP) when compared to venous blood (VEN) draws. Methods Twenty-two adults performed a carbon monoxide rebreathing procedure with paired VEN and CAP draws at baseline, pre-rebreathing and post-rebreathing (POST). Thirteen of these participants performed this protocol on two occasions to assess the data reliability from both blood sampling sites. In a second experiment, 14 adults performed a 20-minute seated and supine rest prior to the rebreathing protocol to assess for the effect of posture. Results Haemoglobin mass (CAP = 948.8 ± 156.8 g; VEN = 943.4 ± 157.3 g, p=0.108) and intravascular volume (CAP = 6.5 ± 1 L; VEN = 6.5 ± 0.9 L, p = 0.752) were statistically indifferent, had low bias (Hbmass bias = 14.45 ± 40.42 g, LoA -64.78 g – 93.67 g) and were highly correlated between sampling techniques. Reliability analysis demonstrated no difference in the mean change in variables calculated from both sampling sites and good to excellent intraclass correlation coefficients (>.700), however, typical measurement error was larger in variables measured using CAP (VEN Hbmass TE% = 2.1%, CAP Hbmass TE% = 5.5%). A supine rest prior to the rebreathing protocol had a significant effect on haemoglobin concentration and haematocrit values compared to a seated rest, with no effect on carboxyhaemoglobin %. Conclusion The present study demonstrates that CAP and VEN were comparable for the calculation of Hbmass and intravascular volumes in terms of accuracy. However, reduced reliability and increased error in the CAP variables indicates that there are methodological considerations to address when deciding which blood drawing technique to utilise. To reduce this CAP error, increased replicate analyses are required.